Queuing, takeovers, and becoming a fat cat: Long‐term data reveal two distinct male spatial tactics at different life‐history stages in Namibian cheetahs. Issue 6 (28th June 2018) - Melzheimer, Joerg; Streif, Sabrina; Wasiolka, Bernd; Fischer, Manuela; Thalwitzer, Susanne; Heinrich, Sonja K.; Weigold, Annika; Hofer, Heribert; Wachter, Bettina
Abstract: In mammals, male spatial tactics and sociality can be predicted from the size, degree of overlap and ease of defense of female individual or group home ranges (HRs). An exception is apparently the cheetah ( Acinonyx jubatus ) for which studies from East Africa describe a socio‐spatial organization where resident males defend small territories, which cover a portion of large ranges of solitary females, and non‐territorial males (floaters) roam over vast areas whilst queuing for access to territories. Most studies from southern Africa did not report the existence of territorial males and floaters, but a system with both males and females roaming over vast areas with overlapping HRs. Here, we derive and test predictions from previously described spatial tactics in felids by studying the movements, behavior, and/or physical characteristics of 164 radio‐collared Namibian cheetahs on commercial farmland from 2002 to 2014. The results demonstrate the existence of male territory holders and floaters and a, by mammalian standards, unique sociality in that commonly groups of males, sometimes solitary males defended small areas partially overlapping with large ranges of solitary females. When a solitary male or a group of males switched between both tactics, floating usually preceded territory holding, suggesting that both spatial phases are equivalent to distinct life‐history stages. Switching from roaming as a floater to holding a territory was also associated with an increase in body mass index (BMI) and a change in the observed behavior of animals captured in traps when approached by humans. Both BMI and this behavior are therefore reliable, quick biomarkers of an individual's space use tactic and life‐history stage. We elaborate the implications of this socio‐spatial organization for models of ecological movements and on conflict mitigation measures such as translocations or the planning of future protected areas. We suggest that such implications also apply to other species where one sex exhibits two space use tactics and two sets of range sizes.